Investigation of the Dynamic Breakdown of a Dielectric Elastomer Actuator Under Cyclic Voltage Excitation - Liu, Xuejing; Xing, Yu; Sun, Wenjie; Zhang, Zhouqiang; Guan, Shengqi; Li, Bo (Frontiers in Robotics and AI, 2021)
Dielectric elastomer (DE) is a new kind of functional polymers, which can be used as smart actuators due to the large deformation induced by voltage excitation. Dielectric elastomer actuators (DEAs) are usually excited by dynamic voltages to generate alternating motions. DEAs are prone to premature breakdown failure during the dynamic excitation, while the research on the breakdown of DEAs under cyclic voltage excitation is still not fully revealed. In this paper, the dynamic breakdown behavior of DEAs made from VHB4910 film were experimentally investigated. Affecting factors for breakdown behavior of DEAs under dynamic voltages were determined and the relevant changing laws were summarized accordingly. The experimental results show that under dynamic voltage excitation, the critical breakdown voltage of DEAs augmented slowly with voltage frequency and showed a substantial dispersion. In addition, the maximum cycle numbers before breakdown were significantly affected by voltage parameters (such as frequency, amplitude, waveform). Finally, the underlying mechanisms of breakdown under cyclic voltages were discussed qualitatively and a power-law equation was proposed to characterize the maximum cycle number for dynamic breakdown of DEA and related parameters were fitted. This study provides a new path to predict service life of DEA under dynamic voltage.